Kajian dan Implementasi Real Time Operating System pada Single Board Computer Berbasis Arm - A, Wiedjaja; M, Handi; L, Jonathan; Christian, Benyamin; Kristofel, Luis (Bina Nusantara University, 2014)
Operating System is an important software in computer system. For personal and office use the operating system is sufficient. However, to critical mission applications such as nuclear power plants and braking system on the car (auto braking system) which need a high level of reliability, it requires operating system which operates in real time. The study aims to assess the implementation of the Linux-based operating system on a Single Board Computer (SBC) ARM-based, namely Pandaboard ES with the Dual-core ARM Cortex-A9, TI OMAP 4460 type. Research was conducted by the method of implementation of the General Purpose OS Ubuntu 12:04 OMAP4-armhf-RTOS and Linux 3.4.0-rt17 + on PandaBoard ES. Then research compared the latency value of each OS on no-load and with full-load condition. The results obtained show the maximum latency value of RTOS on full load condition is at 45 uS, much smaller than the maximum value of GPOS at full-load at 17.712 uS. The lower value of latency demontrates that the RTOS has ability to run the process in a certain period of time much better than the GPOS.